Proceedings of South Carolina Environmental Education Conference (Hobcaw House, Georgetown, South Carolina, February 3-4, 1971) - South Carolina State Dept. of Education, Columbia; South Carolina State Dept. of Education, Columbia ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1971)
The South Carolina Environmental Education Conference was held February 3 and 4, 1971, at Hobcaw House, Georgetown, South Carolina. The Conference was intended to provide a dialogue between teacher-training institutions, State Department of Education personnel, and other state agency personnel interested in environmental education. One aim of the Conference was to encourage college and university education departments to incorporate the use of available environmental education materials into their curriculums. Addresses, accompanied by resulting discussions and suggestions, are presented verbatim in this report. Topics include: The Need for Environmental Education as an Integral Part of Teacher Education; Existing Teacher Training Programs and Material; Federal Programs as a Source of Funds; Existing Materials for Environmental Education; Principal Parts of a Model Program; Employment Opportunities; Implementation; and Evaluation of Environmental Education Programs. Lists of conference members, staff, and environmental education materials available from the South Carolina State Department of Education are included. (BL)
Sponsoring Agency: Belle W. Baruch Foundation, Clemson, SC.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Conference Reports; Curriculum Development; Educational Programs; Environmental Education; Teacher Education; South Carolina